Analisis Kualitas Air Hujan Sebagai Sumber Air Minum Terhadap Kesehatan Masyarakat (Studi Kasus di Kecamatan Bangko Bagansiapiapi) - Anuar, Khairil; Ahmad, Adrianto; Sukendi, Sukendi (Universitas Riau, 2015)
This study was conducted from May 2013 - May 2014. Locations research wasconducted in the District of Bangko Bagansiapiapi. This study aims to determine the qualityof rainwater as a source of public drinking water in the District of Bangko Bagansiapiapi,knowing the health effects of consuming rainwater as drinking water and contribute ideas forthe Government of Rokan Hilir to be able to hold clean water for the people of the District ofBangko Local Government of Rokan Hilir . The results were obtained as follows: (1). Thequality of rainwater in the study site based on the results of laboratory parameters in terms ofinorganic chemistry, physical parameters, chemical parameters still below the drinking waterquality standards that are required by Minister Regulation No. 492 / Menkes / Per / IV / 2010showed that the rain water at the study site that rain water can be consumed by the public andis not harmful to health.